VIBRATIONALLY MEDIATED PHOTODISSOCIATION OF H2O2 (4-UPSILON-OH) - ROTATIONAL STATE DEPENDENT PHOTODISSOCIATION CROSS-SECTIONS AND VIBRATIONAL-STATE MIXING - Brouard, M; Mabbs, R (1993)
A reinvestigation of the vibrationally mediated photodissociation spectrum of the 3rd OH stretching overtone (4vOH) of jetcooled H2O2, first observed by Crim and co-workers, reveals anomalous double resonance spectral intensities compared with those observed via high-resolution absorption spectroscopy. The origin of these intensity perturbations is traced to J'KaKc level dependent variations in the photodissociation cross section, δ00, out of the intermediate overtone state. The photofragment OH(X, v=0) rotational state distribution generated by photodissociation of H2O2 (4vOH, J'KaKc=202) has been determined. Combined with the relative cross-section data, these results imply that delocalization of the overtone state wavefunction into wideamplitude OO stretching regions of the ground state is profoundly influenced by parent molecular rotation, primarily about the a and b axes. The intermediate state with J'=0 is shown to be much more highly localized, and hence more likely to display mode selective behaviour, than its J' >0 counterparts. © 1993.